2020
DOI: 10.1021/acsomega.0c01154
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Aggregation in Aqueous Solution Using Different Water Models: A Classical Molecular Dynamics Study

Abstract: The aggregation behavior of asphaltene in aqueous solution is systematically investigated based on a classical molecular dynamics study. In this work, a novel approach is adopted in order to investigate the structural and dynamical properties of the asphaltene nanoaggregates using different water models. The end-to-end distance of the asphaltene molecule is probed in order to understand the aggregation behavior in aqueous solution. The accuracy of different water models, that is, simple point charge, TIP4P-D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The extended chain length for asphaltene is found to be 24.5 Å. The aliphatic sidechains can change the persistence length in aqueous solution [40] and in organic solvents. The stiffer aliphatic side chains are found on shorter length scales and the longer length scale side chains bend to participate in the aggregation process.…”
Section: Key Stepsmentioning
confidence: 93%
See 2 more Smart Citations
“…The extended chain length for asphaltene is found to be 24.5 Å. The aliphatic sidechains can change the persistence length in aqueous solution [40] and in organic solvents. The stiffer aliphatic side chains are found on shorter length scales and the longer length scale side chains bend to participate in the aggregation process.…”
Section: Key Stepsmentioning
confidence: 93%
“…The distance between one end of the aliphatic side chain to the other end is termed as the end-to-end distance. This distance is crucial in understanding the aggregation behaviour of asphaltenes in aqueous solution as established by one of our previous works [40]. In this study, we probed the end-to-end distance to understand the aggregation behavior of asphaltenes in hexane and toluene mixture considering the semi-flexible side chains [41] within the worm-like chain model [42].…”
Section: End-to-end Distancementioning
confidence: 93%
See 1 more Smart Citation
“…In the heavy crude oil, the asphaltene component holds the major fraction . Asphaltenes form aggregates in n -alkanes, water, and water–oil emulsion and are responsible for the high viscosity of crude oil. , The chemical treatment of asphaltenes is done using cyclic aromatic compounds, such as benzene, toluene, xylene, and pyridine, in which asphaltene is soluble. These solvents are, however, hazardous and volatile.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, four different solvent mixtures were considered, their results showed that pure CO 2 enhances hydrogen bond formation and dipolar interaction between aggregating molecules. The aggregation behavior of Asphaltene in aqueous solution was studied by Vatti et al [23], in the study, Violanthrone-97 was considered as the model Asphaltene compound while three water models were considered. The results obtained from the study emphasized the importance of using appropriate water models in studying the aggregation behavior of Asphaltenes.…”
Section: Introductionmentioning
confidence: 99%